THE IMPLEMENTATION MODEL OF FINANCIAL STATEMENTS-BASED GROUP SYSTEM TO INCREASE REVENUE ON THE CREATIVE INDUSTRY - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The purpose of this research program was to know: the Implementation Model of Financial Statements-based Group System to Increase Revenue on the Creative Industry in Kayubihi Village. The method used was qualitative method with terminal implementation. The data is qualitative. The results of the research show that: (1) the averages of Implementation based on Knowledge and skills about simple financial entry in doing the business: 94.4% of bamboo wicker craftsmen; Knowledge about simple financial entry: 87.8% of the craftsmen; Skills about simple financial entry according to the trained: 91.2% of the craftsmen. (2) after understanding and mastering on how too make a simple financial entry, the craftsmen claimed that they no longer experience an error in determining the selling price, (3) household expenditures and business expenditures activities are now separated, (4) the wages determination for employees is adjusted to the revenues earned from business results.Keywords: financial; group system; creative industry